Pengaruh Psikologis, Harga dan Tampilan Produk Terhadap Impulsive Buying Generasi Z dengan Tren Sebagai Variabel Intervening di Shopee - Syahwa Putriyani; Abdul Aziz (Pusat Riset dan Inovasi Nasional, 2025)
The objective of this research is to determine the influence of psychological behavior, price, and product appearance on impulsive buying on the Shopee platform, with trends as an intervening variable. This research employs a quantitative approach and descriptive analysis techniques. The study sampled 71 respondents, consisting of students from the Digital Business program at Universitas Ngudi Waluyo, categorized as Generation Z, ranging from early to final semesters. A probability sampling technique, or random selection, was used. The data were processed and analyzed using partial test methods (t-test) and the Sobel test. The findings of this study reveal that : (i) psychological behavior influences trends; (ii) price influences trends; (iii) product appearance influences trends; (iv) psychological behavior influences impulsive buying; (v) price influences impulsive buying; (vi) product appearance influences impulsive buying; (vii) trends influence impulsive buying; (viii) trends mediate the effect of price on impulsive buying; (ix) trends mediate the effect of psychological behavior on impulsive buying; (x) trends mediate the effect of product appearance on impulsive buying.